Digitalisasi Pemasaran Kain Tenun Desa Kalena Wanno: Pengembangan Sistem Informasi Berbasis Web - Marselina Anjela Bangnga; Ardiyanto Dapadeda; Felysitas Ema Ose Sanga (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
Sumba woven fabrics have developed into a global market commodity sought after by collectors and tourists. However, artisans in Kalena Wanno Village still face limitations in traditional marketing channels. This study aims to develop a website as a means of promotion and sales to expand market access and improve the welfare of local artisans through technology use. The research method used is descriptive qualitative with a Waterfall model system development approach. The results show that the application of the